Jual Beli Ikan Dalam Keranjang - Vebby Claudia Rizki Pasaribu (Jurnal El-Thawalib, 2021)
The economic factor is one of the reasons for each party to get faster profits. Many ways have been done to fulfill this, such as the practice of buying and selling fish per basket carried out by the parties concerned in Tangkahan Renta Sari Pancuran Bambu Village, Sibolga Sambas District, Sibolga City, where they do not pay attention to the types of fish in it. and what kind of loss effect the prospective buyer and seller will experience. The purpose of this study was to determine how the practice of buying and selling fish per basket in Tangkahan Renta Sari Pancuran Bambu Village, Sibolga Sambas District, Sibolga City, as well as a review of the compilation of sharia economic law on the sale and purchase carried out. The theory used in this research is the theory that is in accordance with the legal basis of buying and selling, pillars and terms, to buying and selling that is prohibited in accordance with the Compilation of Sharia Economic Law. But the difference between the types of fish makes the buyer or trader who wants to buy not know what fish is in the basket and also the buyer cannot see whether the fish is really fresh as said by the Tangkahan officer or the fisherman who sells the fish. And this buying and selling also uses a message system for those who have subscribed, so the technological development that we enjoy today is like a double-edged sword, on the one hand it contributes to increasing prosperity, progress and human civilization in a more practical and instant direction.